Groundwater controls on soil–environment variables and carbon risk in smallholder peatland agriculture of West Kalimantan, Indonesia - Mahardika, Rabbirl Yarham; Fadilla, Ulfia; Azizu, Muhamad Noor; Siregar, Hummaira Hasnaya (Brawijaya University, 2026)
Smallholder agriculture in Indonesia plays an essential role in sustaining local food production and rural livelihoods. However, management practices remain highly variable and frequently lack adequate environmental safeguards. Groundwater table (GWT) is a primary determinant of peat properties and processes. This study examined soil–environment interactions in Kubu Raya, West Kalimantan, under two dominant smallholder land-use systems: mixed crops (MCR) and pineapple monoculture (PNP). Measurements included key biogeochemical indicators, soil properties, and GWT risk score (SGWT) derived from nationally regulated thresholds (25 cm and 40 cm) and an upper limit of 60 cm. Statistical analysis indicated that GWT exerted a significant influence (p<0.05) on soil moisture and temperature, redox potential, and pH in both systems. However, the strength of these responses differed between land uses. SGWT analysis highlighted distinct hydrological contrasts between sites. The mean GWT at MCR (36.18 cm) lies between the 25- and 40-cm thresholds, whereas PNP (46.44 cm) exceeds both. The result showed that MCR accounted for 31.9% of the risk range above 25 cm (SGWTMCR25 = 0.3194), compared with PNP at 61.3% (SGWTPNP25 = 0.6126). When evaluated against the 40-cm threshold, MCR no longer surpasses the limit (SGWTMCR40 = 0), while PNP remains within 32.2% of the 40–60 cm risk interval (SGWTPNP40 = 0.3220). These hydrological differences correspond to higher estimated CO? emission factors in PNP and greater subsidence risk relative to MCR. The results emphasize the need for site-specific assessment to guide GWT-based peatland management for smallholders.